Should we screen patients with hematologic malignancies for COVID‐19?. Issue 5 (8th August 2020) - Rassy, Elie; Khoury‐Abboud, Rita‐Maria; Ibrahim, Nathalie; Assi, Tarek; Samra, Bachar; Hanna, Colette; Karak, Fadi El; Ghosn, Marwan
Abstract: The coronavirus disease (COVID‐19) pandemic has posed several challenges to the hematology community to re‐organize the medical care of patients with hematologic malignancies. Whereas the oncology societies favored a more or less conservative approach which considered the possibility of delaying treatment administration on a case‐by‐case basis, the hematology community guidelines were less stringent and recommended adequate individualized regimens. As countries are de‐escalating the lockdown and the medical community is unable to foresee the end of the current outbreak will and whether the pandemic would eventually come back as a seasonal infection, there is interest in screening of patients with hematology malignancies with COVID‐19 instead of limiting access to curative treatments. The rapidly accumulating knowledge about COVID‐19 allows a better understanding of the diagnostic tools that may be potentially used in screening. Herein, we briefly review the pathophysiology of COVID‐19, the rationale of screening of patients with hematologic malignancies, tools for screening, and available guidelines.